Cardiovascular Toxicity Induced by Chronic Vincristine Treatment - Herradón, Esperanza; González, Cristina; González, Antonio; Uranga, Jose Antonio; López-Miranda, Visitación (Frontiers in Pharmacology, 2021)
Vincristine is an eﬀective anticancer agent for treating leukemias, lymphomas, and solid tumors. In recent years, cardiovascular damage has been described during vincristine treatments. The present study aimed to evaluate cardiovascular toxicity, and possible mechanisms involved, caused by vincristine and whether it remains after the suspension of treatment (sequelae). Adult male Wistar rats were used. The animals were divided into four treatment groups: two groups of saline (0.9% NaCl; saline, sequelae saline) and two groups of vincristine (100 μg/kg; vincristine, sequelae vincristine). Saline or vincristine was administered intraperitoneally in two cycles of 5 days each, leaving a rest period between cycles of 2 days. The final cumulative vincristine dose administered was 1 mg/kg. Sequelae groups correspond with two weeks after stopping treatment with the antitumor agent. At the end of the different experimental protocols, cardiac and vascular functions were analyzed. Alterations in the expression of different proteins in the cardiovascular tissues were also investigated. Chronic treatment with vincristine did not produced significant changes in cardiac function but it provoked a significant endothelial dysfunction in the aorta, as well as a significant decrease in the mesenteric contractile function. These cardiovascular functional alterations disappeared two weeks after the suspension of chemotherapy treatment. Vincristine caused a significant increase in the expression of tumor necrosis factor-alpha (TNFα), endothelial and inducible nitric oxide synthases (eNOS and iNOS), and connexin 43 in cardiac tissue. In the aorta, vincristine caused a slight increase in TNFα expression, a significant increase in expression of eNOS and iNOS, and a significant decrease in the expression of connexin 43. After two weeks of vincristine post-treatment, the increase in TNFα, eNOS and iNOS expression disappeared, but a significant decrease in the expression of connexin 43 was still observed in aorta. In mesenteric arteries, similar data to those found in the aorta were observed. In conclusion, chronic treatment with vincristine causes functional alterations in the vascular function, as well as changes in the expression of TNFα, eNOs, iNOS and connexin 43 in cardiovascular tissues, implicating direct toxicity during its treatment. These functional alterations are transitory and disappear after the suspension of its treatment.